THE INFLUENCE OF ORGANIZATIONAL CULTURE, TRANSFORMATIONAL LEADERSHIP, AND COMPENSATION TO EMPLOYEE ENGAGEMENT AT NON GOVERNMENTAL ORGANIZATION X IN JAKARTA - Satria Akbar Nugroho (International Journal of Social Science, 2023)
Employee engagement in an organization is an important factor in the development of an organization. NGO X which is a non-profit organization is challenged to continue to increase the donations received by NGO X from waqif. The services provided by NGO X during the pandemic were considered by some of the waqif to be inappropriate, it can be seen from the number of waqif who stop donate regularly every month. The purpose of this study is to analyze the effect of organizational culture, transformational leadership, and compensation to employee engagement at NGO X. This research is a quantitative study with data collection method using questionnaire. The population in this study is 220 employees of NGO X. This study uses probability sampling, that is random cluster sampling type, the sample selected is 127 samples. The collected data analyzed using SmartPLS.